Changes of pH in β-Lactoglobulin and β-Casein Solutions during High Pressure Treatment - Karsten Olsen; Bo B. Jespersen; Vibeke Orlien (Journal of Spectroscopy)
The pH changes in the milk systems, β-lactoglobulin B, β-casein, and mixture of β-lactoglobulin and β-casein (pH 7 and ionic strength 0.08 M) were measured in situ during increasing pressure up to 500 MPa. An initial decrease to pH 6.7 was observed from 0.1 to 150 MPa for β-lactoglobulin, followed by an increase to pH 7.3 at 500 MPa. The initial decrease is suggested to be caused by the deprotonation of histidine, while the increase is suggested to result from an increase of hydroxide ions due to the loss of tertiary structure. The change in pH of the β-casein solution displayed an almost linear increasing pressure dependency up to a pH of 7.7 at 500 MPa. The limited tertiary structure of β-casein could allow exposure of all amino acids; thus the increase of pH can be caused by binding of water protons resulting in an increase of hydroxide ions. Addition of β-casein to β-lactoglobulin (1:1) was found to suppress the initial pH decrease found for the β-lactoglobulin solution. The pH change of the mixture did not suggest any intermolecular interaction, and a simple additive model is proposed to calculate the pH change of the mixture from the corresponding individual samples.